Nerve Stimulation Enhances Task-Oriented Training in Chronic, Severe Motor Deficit After Stroke: A Randomized Trial. Issue 7 (July 2016) - Carrico, Cheryl; Chelette, Kenneth C.; Westgate, Philip M.; Powell, Elizabeth; Nichols, Laurie; Fleischer, Anne; Sawaki, Lumy
Abstract : Background and Purpose—: A sensory-based intervention called peripheral nerve stimulation can enhance outcomes of motor training for stroke survivors with mild-to-moderate hemiparesis. Further research is needed to establish whether this paired intervention can have benefit in cases of severe impairment (almost no active movement). Methods—: Subjects with chronic, severe poststroke hemiparesis (n=36) were randomized to receive 10 daily sessions of either active or sham stimulation (2 hours) immediately preceding intensive task-oriented training (4 hours). Upper extremity movement function was assessed using Fugl–Meyer Assessment (primary outcome measure), Wolf Motor Function Test, and Action Research Arm Test at baseline, immediately post intervention and at 1-month follow-up. Results—: Statistically significant difference between groups favored the active stimulation group on Fugl–Meyer at postintervention (95% confidence interval [CI], 1.1–6.9; P =0.008) and 1-month follow-up (95% CI, 0.6–8.3; P =0.025), Wolf Motor Function Test at postintervention (95% CI, −0.21 to −0.02; P =0.020), and Action Research Arm Test at postintervention (95% CI, 0.8–7.3; P =0.015) and 1-month follow-up (95% CI, 0.6–8.4; P =0.025). Only the active stimulation condition was associated with (1) statistically significant within-group benefit on all outcomes at 1-month follow-up and (2) improvement exceeding minimal detectable change, as well as minimal clinically significant difference, on ≥1 outcomes at ≥1 time points after intervention. Conclusions—: After stroke, active peripheral nerve stimulation paired with intensive task–oriented training can effect significant improvement in severely impaired upper extremity movement function. Further confirmatory studies that consider a larger group, as well as longer follow-up, are needed. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02633215. Abstract : Supplemental Digital Content is available in the text.